Naming God: a theological task unfinished. Contributions of Paul Ricoeur. - Rodrigues Rocha, Alessandro (2012)
This paper presentes the Paul Ricoeur´s thought about the most  appropriate language to naming God, from the closing conceptual to the opening polysemic metaphor present in narrativity that is primarily as a back up to the experience